Links Between Motor Control and Classroom Behaviors: Moderation by Low Birth Weight. - Razza, Rachel; Martin, Anne; Brooks-Gunn, Jeanne (Journal of Child & Family Studies, 2016)
It is unclear from past research on effortful control whether one of its components, motor control, independently contributes to adaptive classroom behaviors. The goal of this study was to identify associations between early motor control, measured by the walk-a-line task at age 3, and teacher-reported learning-related behaviors (approaches to learning and attention problems) and behavior problems in kindergarten classrooms. Models tested whether children who were vulnerable to poorer learning behaviors and more behavior problems due to having been born low birth weight benefited more, less, or the same as other children from better motor control. Data were drawn from the national Fragile Families and Child-Wellbeing Study ( n = 751). Regression models indicated that motor control was significantly associated with better approaches to learning and fewer behavior problems. Children who were low birth weight benefitted more than normal birth weight children from better motor control with respect to their approaches to learning, but equally with respect to behavior problems. Additionally, for low but not normal birth weight children, better motor control predicted fewer attention problems. These findings suggest that motor control follows a compensatory model of development for low birth weight children and classroom behaviors.